E eu não sou uma mulher?: silêncios sobre a violência doméstica contra as mulheres negras em Pernambuco. - Neves, Ciani Sueli das (2022)
This doctoral dissertation belongs to the field of interdisciplinary studies regarding human rights, law, and feminism. More specifically, its subject of study is violence against women and racism. It considers how the approaches put forward by classical feminism theory, by silencing the discussions about racism, collaborated with the sexism of domestic and family violence against black women in trying to mask the problem at hand. Consequently, when black women are victimized, there are many difficulties identifying adequate ways to face the aforementioned type of violence. Furthermore, there is a detrimental limitation on the efficiency of public policies thought to ensure their protection. Because black women have the recognition of their humanity denied by racism, they are turned into the main target of dehumanizing practices, being held responsible for the criminalization and banalization of the violation of their rights. This research established a dialogue between anti-incarceration feminism and decolonial feminism and identified the necessity for black women’s selforganization to intervene in a qualified manner in public policies ensuring oversight of the State’s conduct. Pernambuco’s Black Women Association contributes to the protection of black women’s rights and furthers grassroots movements with equal intent. The group was an important interlocutor during the development of this dissertation. For this research, it was used a qualitative methodology, collecting data through questionnaires and semi-structured interviews with black women residing in the state of Pernambuco. The results were presented dialogically with those produced by the bibliographic research on domestic and family violence against black women, as well as the perceived silences on the matter. The methodological path traced was grounded on a critical study of the readings regarding the different manifestations of violence and its continuity to assess how racial sexual and class oppressions simultaneously structure and enhance racist and sexist inequities imposed on black women.